Advancing Discontinuous-Model Predictive Control for High Performance Inverters via Optimized Zero-Voltage State Selection Based on Offset Voltage - Eui-cheol Shin; Hyeon-gyo Chae; Chan Roh (Applied Sciences)
Electric propulsion ships have garnered significant attention for addressing the environmental impact associated with conventional shipping vessels. Their performance critically depends on the inverters that control propulsion motors. This study aims to enhance inverter control by addressing the limitations of conventional model predictive control (MPC), particularly its high current errors and total harmonic distortion (THD) owing to the limited switching frequency. Herein, a discontinuous MPC is proposed that is capable of reducing the switching losses by implementing discontinuous switching during high current periods. This approach employs zero-voltage vectors that are selected based on the polarity of the offset voltage to prevent unnecessary switching losses. Experimental results indicate that the proposed approach reduces the current error by up to 45%, THD by up to 30%, and switching losses by 15–25%. Therefore, this study demonstrates the potential of the proposed control strategy to improve the efficiency and reliability of electric propulsion systems, thereby contributing to the advancement of inverter control technology and development of eco-friendly shipping vessels.